The ischemic cascades in contemporary patients: five distinct phenotypes assessed by ABCDE stress echocardiography. (4th February 2022) - Zagatina, A; Ciampi, Q; Cortigiani, L; Wierzbowska-Drabik, K; Haberka, M; Djordjevic-Dikic, A; Boshchenko, A; Rigo, F; Simova, I; Dodi, C; Gaibazzi, N; Morrone, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Stress Echo 2020 study group of the Italian Society of Echocardiography and Cardiovascular Imaging (SIECVI) Background: The classical pathophysiological cornerstone of stress cardiac imaging is the ischemic cascade: alterations in coronary flow velocity reserve (CFVR) come first, regional wall motion abnormalities (RWMA) second, and global alterations of left ventricular diastolic and systolic function last. Aim: To evaluate the ischemic cascade with stress echo (SE) assessed with ABCDE protocol. Methods: We analyzed 1616 patients (age 66 ± 10 years, 1156, 72% males) with chest pain and angiographically documented coronary artery disease (CAD): 928 (57.4%) with previous myocardial infarction and 1451 (89.8%) with previous coronary revascularization. CAD patients were studied with ABCDE-SE protocol by 13 certified laboratories of 5 countries. Stress modality was exercise in 427 (26.4%) dobutamine in 173 (10.7%) and vasodilator stress in 1016 (62.9%) patients (dipyridamole in 982 – 60.8% and adenosine in 34 – 2.1% patients). Step A assessed RWMA; step B, B-lines (diastolic function); step C, left ventricular contractile reserve based on force; step D, CFVR in left anterior descending artery; step E, heart rate reserve. SE response ranged from score 0 (all steps normal) to score 5 (all steps abnormal). Follow up was obtained in all patients. Results: Results were abnormal in 350 (21.7) % for step A, 572 (35.4%) for B, 666 (41.2%) for C, 546 (33.5%) for D and 643 (39.8%) for E. The distribution of positivity is shown in figure. The dominant "solitary phenotype" (only one biomarker abnormal during the test) was step A in 10 (0.6%), step B in 124 (7.7%) step C in 100 (6.2%), step D in 64 (4.0%) and step E in 157 (9.7%) patients. The overall sensitivity for CAD detection including each step of ABCDE score (≥1) was 95.7%. During median follow-up of 22 months [IQ range: 13-37 months] 279 coronary revascularizations occurred. ABCDE score predicted coronary revascularization with score 1: HR: 3.182, 95% CI: 1.699-6.067; score 2: HR: 4.921, 95% CI: 2.571-9.420; score 3: HR: 7.234, 95% CI: 3.743-13.979; score 4: HR: 24.570, 95% CI: 13.390-45.086; and score 5: HR: 38.720, 95% CI: 20.975-71.478 Conclusion: Inducible ischemia with CAD is characterized by the complexity and multiplicity of diagnostic phenotypes. The overall ABCDE score predicts clinically driven revascularization.